Clinical Efficacy of Minimally Invasive Elastic Stable Intramedullary Nailing for Limb Long Bone Fractures in Children. Issue 4 (7th May 2021) - Dong, Liangchao; Wang, Yichen; Jiao, Qin; Wang, Sun
Abstract : Objective: The aim of the present paper was to investigate the clinical efficacy of minimally invasive elastic stable intramedullary nailing (ESIN) for long bone fractures in children. Methods: A total of 350 children with limb fractures from June 2012 to June 2018 were recruited and randomized into two groups: an ESIN group ( n = 175) treated with elastic stable intramedullary nailing, and an MPIF group ( n = 175), treated with metal plate internal fixation. Both groups received the same physical examination and routine medication. Operation related indexes, clinical efficacy, complications, and postoperative quality of life scores were analyzed and compared. Results: The operation time, intraoperative blood loss, hospitalization time, and fracture healing time in the ESIN group were 43.74 ± 4.96 min, 8.14 ± 1.34 mL, 5.97 ± 1.88 days, and 55.89 ± 5.61 days, respectively, which were all significantly less than those in the MPIF group (all P < 0.001). In terms of common complications after limb fracture treatment, there were 6 cases of osteomyelitis, 5 cases of skin irritation response, and 7 cases of inflammatory granuloma in the MPIF group. There were 2 cases of skin irritation response and 5 cases of inflammatory granuloma in the ESIN group. The incidence of postoperative complications in the ESIN group was 4.00%, which was significantly lower than that in MPIF group (10.29%) ( P < 0.05). The effective rate for recovery condition in the ESIN group (93.71%) was significantly higher than that in the MPIF group ( P < 0.001). The quality of life scores after treatment in both groups were improved, while the score in the ESIN group was significantly higher than that in the MPIF group (79.43%) ( P < 0.001). The postoperative satisfaction rate in the ESIN group (94.29%) was significantly higher than that in the MPIF group (86.29%) ( P < 0.05). The quality of life scores after treatment in both groups were improved, while the score in the ESIN group was significantly higher than that in the MPIF group ( P < 0.001). The postoperative satisfaction rate and the acceptance rate for adjacent joint function in the ESIN group (100%) were significantly higher than those in the MPIF group (92.00%) ( P < 0.0001). Conclusion: Elastic stable intramedullary nailing is a minimally invasive procedure for long bone fractures in children. It can effectively improve the operation‐related indicators and postoperative quality of life and reduce the incidence of complications. Abstract : Workflow of clinical research. Note: TEN, titanic elastic nailing.